A form of motor cortical plasticity that correlates with recovery of function after brain injury - Ramanathan, Dhakshin (National Academy of Sciences, 2006)
To investigate functional mechanisms underlying cortical motor plasticity in the intact and injured brain, we used “behaviorally relevant,” long-duration intracortical microstimulation. We now report the existence of complex, multijoint movements revealed with a 500-msec duration intracortical stimulation in rat motor cortex. A consistent topographic distribution of these complex motor patterns is present across the motor cortex in naïve rats. We further document the plasticity of these complex movement patterns after focal cortical injury, with a significant expansion of specific complex movement representations in response to rehabilitative training after injury. Notably, the degree of functional recovery attained after cortical injury and rehabilitation correlates significantly with a specific feature of map reorganization, the ability to reexpress movement patterns disrupted by the initial injury. This evidence suggests the existence of complex movement representations in the rat motor cortex that exhibit plasticity after injury and rehabilitation, serving as a relevant predictor of functional recovery.